Proceedings of the 25th ACM Conference on Hypertext and Social Media 2014
DOI: 10.1145/2631775.2631805
|View full text |Cite
|
Sign up to set email alerts
|

Reader preferences and behavior on Wikipedia

Abstract: Wikipedia is a collaboratively-edited online encyclopaedia that relies on thousands of editors to both contribute articles and maintain their quality. Over the last years, research has extensively investigated this group of users while another group of Wikipedia users, the readers, their preferences and their behavior have not been much studied. This paper makes this group and its activities visible and valuable to Wikipedia's editor community. We carried out a study on two datasets covering a 13-months period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Our prior work has showed that popularity can play an important role in the estimation of quality in specific language versions of Wikipedia [5]. Other studies have showed that measuring a topic's popularity in English Wikipedia can help in determining its number of articles of good quality-if the topic is popular, then it has a larger number of high-quality articles [19]. Warncke-Wang et al showed misalignment between the popularity and quality of the articles in Wikipedia; however, the study was limited to four language versions of Wikipedia [20].…”
Section: Popularity Measuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Our prior work has showed that popularity can play an important role in the estimation of quality in specific language versions of Wikipedia [5]. Other studies have showed that measuring a topic's popularity in English Wikipedia can help in determining its number of articles of good quality-if the topic is popular, then it has a larger number of high-quality articles [19]. Warncke-Wang et al showed misalignment between the popularity and quality of the articles in Wikipedia; however, the study was limited to four language versions of Wikipedia [20].…”
Section: Popularity Measuresmentioning
confidence: 99%
“…Similarly to other studies [19,20], we have used the page view information in order to measure the popularity of articles. Wikipedia records data on users visiting their pages in all language versions every hour to special compressed files (https://dumps.wikimedia.org/other/analytics/).…”
Section: Popularity Measurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to time patterns for consumption, consumer preference can be analysed by topic. Lehmann, Müller-Birn, Laniado, Lalmas, and Kaltenbrunner (2014) quantified the preference of consumers specific to biographical articles (a popular topic) in the English Wikipedia (the largest edition) and found that biographies of historical figures, general history, places and culture were rated among the 500 most popular articles. Geography, history and politics have been identified as highly popular topics, which Spoerri (2007a) defined as prototypical encyclopaedia topics.…”
Section: Consumption Patterns In Wikipediamentioning
confidence: 99%
“…Researchers have focused on predicting article quality in Wikipedia [3,20]. However, focusing on quality without considering readers does not give the whole picture, as Wikipedia readers are not necessarily interested in the same topics as contributors [33] and might have a different concept of quality. Moreover, in our context, Flekova, Ferschke, and Gurevych [20] found that the quality of biographies is assessed differently depending on the gender of the portrayed person.…”
Section: Introductionmentioning
confidence: 99%